Comparing NPS users in nightlife settings and online communities - Henriques, S.; Silva, J. P.; Van Hout, M. C.; Hearne, E.; Benschop, A.; Korf, D.; Bujalski, M.; Wieczorek, Ł.; Werse, B.; Felvinczi, K.; Dąbrowska, K.; Kaló, Z.; et al. (Video Journal of Social and Human Research, 2024)
This article reports on the comparison between two groups of New Psychoactive Substances (NPS) users: users in nightlife settings and users in online communities. A quantitative survey was conducted in six EU countries (Germany, Hungary, Ireland, Netherlands, Poland, and Portugal) within a convenience sample of adult (18 years+) current (12-month) NPS users. Participants self-completed either a pen-and-paper or online questionnaire. 2,757 respondents across the six European countries were reached during data collection in the two considered user groups. The comparison was based on sociodemographic characteristics, use patterns and market. The groups of NPS used are: herbal blends and/or synthetic cannabinoids; branded stimulants and/or stimulants/Empathogenics/nootropics obtained pure; psychedelics; dissociatives; and other NPS. Internet and virtual markets assume great relevance both for nightlife and online communities. Different drug policies and diverse geographical location between the participant countries are the main characteristics that impact on the results-namely in the presence/absence of some substances, or in the legal concept of NPS. Comparing users in nightlife settings and online users highlighted substantive trends in NPS use across countries and user groups. New opportunities in the drug market were driven by technological developmentson the internet.